Perceived effort in football athletes: the role of achievement goal theory and self-determination theory - Monteiro, Diogo (2018)
This study examined the motivational determinants of athletes perceived effort in football considering the four-stage motivational sequence at the contextual level proposed by Hierarchical Model of Intrinsic and Extrinsic Motivation: task-involving climate, basic psychological needs, self-determined motivation (SDM), and perceived effort. Additionally, SEM multi-group analysis across different age-groups (U15, U17, U19, and U21 years) and serial mediation of basic psychological needs (BPNs) and SDM on the task-involving motivational climate and the perceived effort were also analyzed. Two independent samples of male football athletes (N = 403, N = 403), aged 13-20 years were enrolled in this study. The results support the adequacy of the structural model in explaining the perceived effort of football atheltes in all samples under analysis, and was invariant across U17, U19, and U21. However, it was not invariant across U15 and U17, U19 and U21. Furthermore, results from the serial mediation showed significant indirect effects in all samples, supporting self-determination theoretical assumptions, reinforcing the importance of BPNs satisfaction and behavioral regulation in the relation in analysis. The results show that when coaches promote a task-involving climate, the BPNs satisfaction of athletes improves. This climate will facilitate the regulation of their behaviors toward more autonomous forms of motivation, with positive outcomes in the athletes perceived effort.